Soil microbial inoculants for sustainable agriculture: Limitations and opportunities - O'Callaghan, Maureen; Ballard, Ross A.; Wright, David (Soil use and management, 2022)
The burgeoning global market for soil microbial inoculants for use in agriculture is being driven by pressure to increase sustainable crop production by managing pests and diseases without environmental impacts. Microbial inoculants, based predominantly on bacteria and fungi, are applied to soil as alternatives to conventional inorganic fertilizers (biofertilizers) or to carry out specific functions including biocontrol of pests and diseases (biopesticides), or for bioremediation and enhancement of soil characteristics. While some soil inoculants such as rhizobia have a long and successful history of use, others have performed inconsistently in the field and failed to live up to their promise suggested by laboratory testing. A more precise understanding of the ecology and modes of action of inoculant strains is key to optimizing their efficacy and guiding their targeted use to situations where they address key limitations to crop production. This will require greater collaboration between science disciplines, including microbiology, plant and soil science, molecular biology and agronomy. Inoculants must be produced and formulated to ensure their effective establishment in the soil and practicality of implementation alongside existing cropping practices. New approaches to strain selection and construction of beneficial microbial consortia should lead to more efficacious inoculant products. Extensive and rigorous field evaluation of inoculants under a range of soil and environmental conditions has rarely been undertaken and is urgently needed to validate emerging inoculant products and underpin successful implementation by growers, especially in a market that is largely unregulated at present.